J2EE™ and JAX™: Developing Web Applications and Web Services - Yawn, Michael (Hewlett-Packard professional books., 2002)
Learn J2EE and the JAX APIs for Web services and applications-all in one volume. The first book to offer integrated coverage of J2EE and JAX in one volume Java Web application and services programming taught by example Rich with code examples and explanations of supporting technologies CD-ROM includes free, fully functional copy of HP Application Server (HP-AS) Using a simple, stand-alone program as a point of departure, Java expert Michael Yawn brings you through all the steps and decisions needed to transform it into a rich, Web-enabled application. Along the way you'll gain a working knowledge of Java 2 Enterprise Edition (J2EE) and the Java APIs for XML (JAX)-emerging technologies for writing Web applications and working with XML documents and procedures. Yawn's technique of reworking the example application gives you hands-on experience at adapting software for different purposes and environments, as well as a deep understanding of how to build flexibility into your projects from the outset. Web applications and services-and underlying technologies-by example Layering applications to simplify reworking; using design patterns Integrating JavaServer Pages, JavaBeans, Servlets, and custom tag libraries XML on the Web and with wireless devices Java Message Service, MOM, and XML messaging with SOAP and JAXM JAX RPC services and their clients Enterprise JavaBeans-Session, Message-Driven, and Entity beans CD-ROM contains a full copy of HP Application Server (HP-AS)-a free alternative to IBM's WebSphere and BEA's WebLogic-and code samples from the book In his engaging style, Yawn doesn't simply describe Web applications and services-you'll come away understanding how it all fits together. With the whys well in hand, you'll be a much more effective coder. This book requires only a basic knowledge of Java programming, and its content is applicable to all servers.